The PHOX2B c.428A>G missense variant affects post-transcriptional regulation and may explain the absence of neural crest-derived tumors in congenital central hypoventilation syndrome - Bachetti, Tiziana; Bagnasco, Simona; Santamaria, Giuseppe; Bedeschi, Maria Francesca; Menni, Francesca; Catalano, Igor; Spaccini, Luigina; Cavigioli, Francesco; Morandi, Francesco; Ceccherini, Isabella (Frontiers in Physiology, 2025)
IntroductionHeterozygous mutations in the paired-like homeobox 2b (PHOX2B) gene cause congenital central hypoventilation syndrome (CCHS). While polyalanine expansions are almost exclusively associated with isolated CCHS, missense, nonsense, and frameshift mutations are mainly identified in syndromic CCHS, presenting with Hirschsprung disease (CCHS + HSCR) alone and/or together with neuroblastoma (CCHS + HSCR + NB). CCHS-associated missense mutations occur in the PHOX2B homeodomain, where impaired transcriptional activity has been suggested as their functional effect. However, the molecular pathogenesis underlying their association with HSCR- and/or NB-associated CCHS has not been investigated to date.Methodswe applied an in silico analysis and a minigene approach in vitro to test the effect of the PHOX2B c.428A>G missense variant on the splicing of intron 2.Resultswe demonstrate that the missense c.428A>G variant, reported by us and others in a set of CCHS + HSCR cases but never associated with NB, not only causes the amino acid change p.Q143R change but also disrupts the intron 2 splice donor site, producing an aberrant mRNA transcript and likely a hypomorphic, dysfunctional protein.DiscussionWe, therefore, propose that in the presence of splicing defects of PHOX2B, a loss-of-function mechanism may underlie CCHS + HSCR and potentially explain the absence of neural-crest-derived tumors.